Em direção à costa brasileira fugindo do inverno: rotas migratórias contrastantes e plasticidade diferencial dos astrócitos hipocampais - OLIVEIRA, Marcus Augusto de (Universidade Federal do Pará, 2019)
One of the largest seasonal events on the planet is the migration of birds from the Arctic to the southern hemisphere fleeing from winter and returning to the Arctic during the spring to the breeding season. Billions of individuals need to remember the routes learned during this epic journey and find the same places to rest and feeding. These birds can navigate thousands of miles with great accuracy, utilizing their spatial and temporal memories associated with the hippocampus, a key area for accomplishing this task. Recently, we have shown that the semipalmated sandpiper Calidris pusilla, after crossing the Atlantic towards the coast of South America, revealed significant changes in its hippocampal astrocytes. In fact, the hippocampal astrocytes of birds captured on the coast of Bragança in Brazil, compared with those of the hippocampus of individuals caught in the Bay of Fundy, Canada, were less numerous and exhibited shrunken branches. In the present work, we used another semipalmated shorebird, Charadrius semipalmatus, which, although having the same start and end points of C. pusilla migration, uses a different migratory strategy, performing a flight over the continent with stops for rest and feeding. Taking advantage of the opportunity offered by contrasting migratory flights, we tested the hypothesis that wintering bird species of the C. semipalmatus caught on the coast of Bragança (Brazil) would show greater morphological complexities than the hippocampal astrocytes of these migratory birds captured in the Bay of Fundy (Canada). Since the stands for food and rest, as well as the constant change in the landscape would constitute an enriched environment of multisensory stimuli, we expected to find in the individuals of C. semipalmatus captured in Bragança, an increase of the complexity, in opposition to the reduction in complexity previously found in C. pusilla. To test this hypothesis, we compared the three-dimensional (3-D) morphological characteristics of the adult C. semipalmatus astrocytes captured in the Bay of Fundy (n = 265 cells) with those of wintering birds captured in the coastal region of Bragança, Brazil, (n = 242 cells), and compared with the results obtained with C. pusilla. The Neurolucida program was used for three-dimensional reconstructions and the hierarchical cluster analysis (Ward’s method) was used to classify cells. This analysis showed two families of astrocytes, which we designated Type I and Type II, based on several morphological characteristics. Contrary to our expectations, Type I and Type II phenotypes showed, on average, independently of the species, lower morphological complexity after migration, and this reduction was significantly higher in Type I than in Type II. The magnitudes of these changes were significantly higher in C. pusilla than in C. semipalmatus. Taken together, these findings suggest that contrasting long-distance migratory flight strategies may differentially affect the astrocyte morphology and that distinct astrocyte morphologies may be associated with different functional roles during migration.